2019
DOI: 10.3389/fgene.2019.00149
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Overexpression of Gclc in Drosophila melanogaster Induces Life Extension With Longevity-Associated Transcriptomic Changes in the Thorax

Abstract: Some effects of aging in animals are tissue-specific. In D. melanogaster neuronal overexpression of Gclc increases lifespan and improves certain physiological parameters associated with health benefits such as locomotor activity, circadian rhythmicity, and stress resistance. Our previous transcriptomic analyses of Drosophila heads, primarily composed of neuronal tissue, revealed significant changes in expression levels of genes involved in aging-related signaling pathways (Jak-STAT, MAPK, FOXO, Notch, mTOR, TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Glutamate cysteine ligase (GCL) is the rate limiting enzyme in the GSH biosynthetic pathway. It has been known for some time that increasing the catalytic (GCLC) and modifying (GCLM) levels globally ( Orr et al, 2005 ) or specifically in neurons ( Moskalev et al, 2019 ) extends longevity in Drosophila by between 25 and 50%. Overexpressing GCLM increases cellular glutathione content 2-fold, protecting cells from oxidative stress ( Moskalev et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate cysteine ligase (GCL) is the rate limiting enzyme in the GSH biosynthetic pathway. It has been known for some time that increasing the catalytic (GCLC) and modifying (GCLM) levels globally ( Orr et al, 2005 ) or specifically in neurons ( Moskalev et al, 2019 ) extends longevity in Drosophila by between 25 and 50%. Overexpressing GCLM increases cellular glutathione content 2-fold, protecting cells from oxidative stress ( Moskalev et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides antioxidant enzymes directly involved in the detoxification of ROS, another strategy to manipulate cellular redox state in vivo is to target enzymes that provide reducing equivalents for the recycling of antioxidant systems and redox couples. For instance, overexpression of glutamate-cysteine-ligase (GCL), which catalyses the rate-limiting step in the synthesis of GSH, increased lifespan in flies [44,45]. Similarly, overexpression of glucose-6-phosphate dehydrogenase (G6PDH), an enzyme belonging to the pentose phosphate pathway (PPP) involved in the generation of NADPH, robustly extended fly lifespan [46].…”
Section: The Connection Between Oxidative Stress Redox Signalling Anmentioning
confidence: 99%
“…The phylogenetic results showed that TcGclc grouped with the Coleoptera. These results suggest that TcGclc has typical conserved features, and could have typical conserved functions in insects, such as scavenging free radicals, 26 age-related changes 27 and ecdysteroid biosynthesis. 16 The temporal expression pattern showed that TcGclc genes were consistently expressed during all developmental stages except the egg stage (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The phylogenetic results showed that TcGclc grouped with the Coleoptera. These results suggest that TcGclc has typical conserved features, and could have typical conserved functions in insects, such as scavenging free radicals, 26 age‐related changes 27 and ecdysteroid biosynthesis 16 …”
Section: Discussionmentioning
confidence: 86%